Kajian Kritis terhadap Kitab Tafsir Syaikh Uthaimin, Menganalisis Pendekatan dan Metodologi Tafsirnya - Alif Hibatullah; Alghaniy Pramudya Rizasawan; Johana Salsabillah; Abu Bakar (Syntax Corporation Indonesia, 2024)
A critical study of Shaykh Uthaimin's tafsir is an in-depth attempt to analyze the approach and methodology of exegesis used by this figure. Shaykh Uthaimin, a famous scholar, is known for his work that includes Quranic exegesis. This study explores in detail his famous tafsir,